TRADISI MAKAN PUNDUTAN DI DESA PULAU BETUNG 1970-2025 - Agung Nugroho; Deki Syaputra ZE (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2026)
The tradition of eating pundutan in Pulau Betung Village is a cultural heritage that has been carried out from generation to generation during customary and religious events (such as holidays, weddings, and circumcisions). The main purpose of this tradition is to strengthen social relations, share, and symbolize the harmony and unity of the community. Its implementation in Pulau Betung Village officially began around 1970 and is regulated by local customary law called "Eco Pake." This research adopts the historical method, which involves a series of systematic stages, namely heuristics, source criticism, interpretation, and historiography. In the heuristic phase, the researcher attempts to comprehensively collect all sources of information relevant to the study topic, including written documents, oral information, and artifacts (such as photos of pundutan, activities, and togetherness). The results of this research will present a historical description and an in-depth analysis of the pundutan eating tradition in Pulau Betung Village from 1970 to 2025, obtained through the stages of heuristics, criticism, interpretation, and historiography.